Seryl-tRNA synthetase from Escherichia coli: implication of its N-terminal domain in aminoacylation activity and specificity. - Borel, F (1994)
Escherichia coli seryl-tRNA synthetase (SerRS) a dimeric class II aminoacyl-tRNA synthetase with two structural domains charges specifically the five iso-acceptor tRNA(ser) as well as the tRNA(sec) (selC product) of E. coli. The N-terminal domain is a 60 A long arm-like coiled coil structure built of 2 long antiparallel a-h helices, whereas the C-terminal domain is a alpha-beta structure. A deletion of the N-terminal arm of the enzyme does not affect the amino acid activation step of the reaction, but reduces dramatically amino-acylation activity. The Kcat/Km value for the mutant enzyme is reduced by more than 4 orders of magnitude, with a nearly 30 fold increased Km value for tRNA(ser). An only slightly truncated mutant form (16 amino acids of the tip of the arm replaced by a glycine) has an intermediate aminoacylation activity. Both mutant synthetases have lost their specificity for tRNA(ser) and charge also non-cognate type 1 tRNA(s). Our results support the hypothesis that class II synthetases have evolved from an ancestral catalytic core enzyme by adding non-catalytic N-terminal or C-terminal tRNA binding (specificity) domains which act as determinants for cognate and anti-determinants for non-cognate tRNAs.